Palliative care competencies in nephrology: a scoping review - Mateus, Ana (2022)
Introduction: There is a growing need to train nonpalliative physicians in palliative care, as it is increasingly recognized by the medical profession. Political and opinion leaders are also becoming aware of the urgent and growing need for palliative care education. Objective: The aim of this study is to provide an overview of the information available in the literature on the topic of palliative care competencies for nephrologists, using clearly defined and transparent methods to search, summarize, and interpret the relevant literature based on a systematic review approach. Methods: The scoping review is based on the Joanna Briggs Institute methodology. The search was conducted in December 2019 using publications in national and international databases and grey literature in English, Spanish, French and Portuguese. Results: Of the total 4668 publications, 168 were eligible for review based on title and abstract. A full-text review of these 168 publications resulted in the selection of 27 articles that met the predefined inclusion and exclusion criteria and were therefore included in the study. The following competencies were considered necessary to provide high quality PC in various nephrology settings: Communication skills (21.3%); End-of-life care, loss, grief, and bereavement (18.6%); Control of pain and other renal symptoms (16%); Advance care planning (16%); Ethical and legal issues in dialysis decision making (12.2%); Teamwork (6.6%); Ability to provide psychosocial and spiritual support to patients and families (5.6%). Application of palliative care principles (3.7%). Percentage refers to the number of publications addressing each topic. Conclusion: The implementation of an integrated care model that includes both PC and curative treatments places high demands on nephrologists, who must acquire PC competencies. Training in palliative care should be included in the curricula for nephrologists.